Management Strategy of SMK Negeri 3 Semarang in An Effort to Increase the Absorption Capacity of Graduates through Cooperatives in the Business and Industrial World (DU/DI) - Handayani, Siti; Joko Raharjo, Tri; Yulianto, Arief (Educational Management, 2019)
School management strategy in an effort to increase the absorption capacity of graduates is due to the low absorptive capacity of vocational school graduates in the business and industrial world. One of the indications is influenced by the lack of communication between the school and the business and industrial world. This study aims to describe and analyze the collaboration management of SMK Negeri 3 Semarang with the business and industrial world, starting from planning, implementation, and evaluation. This research is a qualitative research. Sources of data obtained from (1) informants from SMK N 3 Semarang and industry; (2) the process of planning, organizing, implementing, supervising collaboration between SMK N 3 Semarang and the business and industrial world. While data collection techniques are observation, interview and documentation. Data analysis techniques used include the following procedures: (1) data collection in the field; (2) data reduction; (3) data display and (4) verification and conclusion drawing. The results of the study: (1) Planning was completed through: the formulation of the plan by presenting an industry delegate, setting the plan with a plenary meeting attended by the teacher council, parents of students and school committees, and evaluation of the plan by Evabang; (2) Organizing, coordinating and collaborating between vocational high schools and industry to carry out learning in the form of theory by inserting character education, school practice, and practice, (3) Implementation is adjusted to the establishment of plenary meeting plans (4) Evaluation from industry, BAN-S/M and ISO.